Cardiac sodium channel complexes and arrhythmia: structural and functional roles of the β1 and β3 subunits. (3rd December 2022) - Salvage, Samantha C.; Jeevaratnam, Kamalan; Huang, Christopher L.‐H.; Jackson, Antony P.
Abstract: In cardiac myocytes, the voltage‐gated sodium channel NaV 1.5 opens in response to membrane depolarisation and initiates the action potential. The NaV 1.5 channel is typically associated with regulatory β‐subunits that modify gating and trafficking behaviour. These β‐subunits contain a single extracellular immunoglobulin (Ig) domain, a single transmembrane α‐helix and an intracellular region. Here we focus on the role of the β1 and β3 subunits in regulating NaV 1.5. We catalogue β1 and β3 domain specific mutations that have been associated with inherited cardiac arrhythmia, including Brugada syndrome, long QT syndrome, atrial fibrillation and sudden death. We discuss how new structural insights into these proteins raises new questions about physiological function. Abstract : Abstract figure legend Molecular organisation of NaV α‐ and β‐subunits in healthy ventricular myocardium. The cardiac voltage‐gated sodium channel, NaV 1.5, is typically found in multiple locations within ventricular myocytes together with β1 and/or β3, including at the lateral surface membrane, intercalated disc and caveolae. Other neuronal NaV α‐isoforms including NaV 1.1, NaV 1.3 and NaV 1.6 have been identified in the T‐tubules along with both β1 and β3. In the specialised caveolar lipid membranes, NaV 1.5 localises with Kir2.1, in addition to L‐type Ca 2+ channels and other K + channels (not shown). Further functional specialisations arise from unique trans, cell–cell, NaV 1.5 interactions facilitated by the β1 subunit adopting an alternative structural conformation in which the extracellular Ig domains extend across the intercalated discs (inset). The β3 subunit likely also facilitates stabilisation of NaV 1.5 macromolecular complexes in cis (on the same cell), but the relative organisation of the α‐ and β‐subunits is less defined. Image created with BioRender.com.